2018
DOI: 10.1080/15140326.2018.1526872
|View full text |Cite
|
Sign up to set email alerts
|

Technology evolution and long waves: investigating their relation with spectral and cross-spectral analysis

Abstract: The present paper is an empirical exercise that contributes to the debate on whether long-lasting cyclical economic development can be viewed as a deterministic phenomenon or a stochastic process. First, we search for longer lasting, periodically reappearing cycles of GDP per capita in four countries: USA, UK, Germany and France. Second, based on theoretical arguments that stress applied knowledge as a significant driving force, we test its dynamic interrelationship with these countries' economic performance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Notably, the scientific results are quite consistent with the study [15]. To perform cross-spectral analysis, the authors of this paper selected two time series for each country (GDP and patent activity series) and analysed their consistency, in contrast to the selected approach, which investigated the synchronisation of time series for different countries in this study.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Notably, the scientific results are quite consistent with the study [15]. To perform cross-spectral analysis, the authors of this paper selected two time series for each country (GDP and patent activity series) and analysed their consistency, in contrast to the selected approach, which investigated the synchronisation of time series for different countries in this study.…”
Section: Resultssupporting
confidence: 59%
“…To identify long cycles more reliably, the authors of [15] conducted a spectral analysis of the dynamics of world GDP (for 1870-2007) using an improved method for statistical estimation of selected waves. This analysis allowed assessing the statistical significance of K-waves in the dynamics of global GDP and demonstrated their presence at an acceptable level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another group, including Mandel (1980), Gordon (1991), and Kleinknecht (1987, transform the growth rate and then separate the analysis of long fluctuations from the behaviour of shorter ones. A third group, including van Ewijk (1981van Ewijk ( , 1982, Beenstock (1983), Kleinknecht (1992, part 1), and Reijnders (1990), used spectral and cross-spectral analysis, but found little or no empirical support for the Kondtratiev cycle, while Korotayev and Tsirel (2010), Grinin et al (2016), andOzouni et al (2018) found support for it. Van Duijn (1983) found compelling evidence of a global long cycle.…”
Section: Long Waves After Schumpetermentioning
confidence: 99%